Hydrolysis and aminolysis of aldehydes catalyzed by water and amines: Formation of diols/aminol and the implication to atmospheric particle formation. (1st February 2023) - Wei, Yuanyuan; Zhang, Qingzhu; Wang, Wenxing; Wang, Qiao
Abstract: The hydrolysis and aminolysis reactions of aldehydes were proved to be associated with the secondary organic aerosols (SOA) in the atmosphere. However, these reactions are forbidden owing to the high energy barriers. To make these reactions feasible and assess the catalytic ability of water molecules and amines, the hydrolysis and aminolysis of glyoxal (GL) and glycolaldehyde (GA) were investigated using quantum chemical calculations. The results show that water molecules and amines can catalyze effectively the hydrolysis and aminolysis of aldehydes and the catalytic ability of water molecules is stronger than that of methylamine (MA) and dimethylamine (DMA). Glycine (Gly) can play a stronger role than water molecules in the GL/GA hydrolysis and aminolysis reactions owing to the carboxyl group. At low relative humidity and high pollution condition, the effective rate constants of Gly-catalyzed reactions can be comparable to that of water-catalyzed reactions. The results of MD simulations indicate that the products of GL/GA hydrolysis and aminolysis can participate in the new particle formation (NPF) involving sulfuric acid (SA). Highlights: Assessed the catalytic ability of water and amines in the aldehyde hydrolysis and aminolysis. The catalytic ability of carboxyl group in Gly is stronger than that of amino group. The products of GL/GA hydrolysis and aminolysis can participate in the SA-based NPF.